2021
DOI: 10.1108/ijpsm-06-2021-0152
|View full text |Cite
|
Sign up to set email alerts
|

Managing innovation on the public frontline: three approaches to innovation leadership

Abstract: Purpose For decades, there has been a call for the public sector to be more innovative, and there is widespread agreement that managers play a crucial role in meeting this goal. Most studies of innovation management focus on top-level managers, despite the fact that most innovation activities take place on the frontlines, deeply embedded in professional practice. Meanwhile, micro-level studies of innovation tend to focus on the agency of employees, which leaves a knowledge gap regarding the mobilizing role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In a recent reflection piece, service research pioneers Bowen et al. (2023, p. 35) suggested that service leadership “takes the whole organization rather than a narrow organizational facet.” This line of research sheds light on the development of leadership capabilities among frontline workers (Thøgersen, 2022) through the cultivation of sensemaking capacities (Aflaki and Lindh, 2021), resilience or leadership humility (Sok et al. , 2021).…”
Section: Service Leadership – What We Know and What's Missingmentioning
confidence: 99%
“…In a recent reflection piece, service research pioneers Bowen et al. (2023, p. 35) suggested that service leadership “takes the whole organization rather than a narrow organizational facet.” This line of research sheds light on the development of leadership capabilities among frontline workers (Thøgersen, 2022) through the cultivation of sensemaking capacities (Aflaki and Lindh, 2021), resilience or leadership humility (Sok et al. , 2021).…”
Section: Service Leadership – What We Know and What's Missingmentioning
confidence: 99%
“…For social workers, this change means learning new methods to expand their theoretical knowledge and utilization and developing new solutions to problems in these new contexts (Simpson, 2009) and constructing professional authority to continue to gain embedded legitimacy (Stringfellow, 2017). For social service organization, innovation is central to effective service delivery to citizens, and front-line employees are important sources of innovation in public sector organizations (Thøgersen, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the past decade, the public sector has rapidly transitioned from a heavily bureaucratic system toward a more integrated market-based and private sector model of management (De Vries and Nemec, 2013;Thøgersen, 2022) to address the challenges related to productivity, cost savings and service quality, forcing organizations to redesign and re-scope their processes, structures and systems (Hijal-Moghrabi et al, 2020). The United Arab Emirates (UAE) public sector is no exception (Bani-Melhem et al, 2023).…”
Section: Introductionmentioning
confidence: 99%